2022
DOI: 10.1038/s41419-022-04755-3
|View full text |Cite
|
Sign up to set email alerts
|

VDAC1 regulates neuronal cell loss after retinal trauma injury by a mitochondria-independent pathway

Abstract: The voltage-dependent anion channel 1 (VDAC1) was first described as a mitochondrial porin that mediates the flux of metabolites and ions, thereby integrating both cell survival and death signals. In the nervous system, the functional roles of VDAC1 remain poorly understood. Herein, the rat retina was employed to study VDAC1. First, it was observed that even subtle changes in VDAC1 levels affect neuronal survival, inducing severe alterations in the retinal morphology. We next examined the regulation of VDAC1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…A study found that VDAC1 silencing protectes cardiomyocyte from cytotoxic effect of H 2 O 2 as evidenced by reducing in LDH activity and dead cell number (Jiang et al, 2018). Knockdown of VDAC1 inhibits cell death on in vitro model of oxidative stress (de Sousa et al, 2022). Moreover, VDAC1 inhibitor suppresses the generation of intracellular ROS in macrophages (Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A study found that VDAC1 silencing protectes cardiomyocyte from cytotoxic effect of H 2 O 2 as evidenced by reducing in LDH activity and dead cell number (Jiang et al, 2018). Knockdown of VDAC1 inhibits cell death on in vitro model of oxidative stress (de Sousa et al, 2022). Moreover, VDAC1 inhibitor suppresses the generation of intracellular ROS in macrophages (Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis reveals that the EMC-associated VDAC1 is located at mitochondria-ER contact sites and the EMC-VDAC1 interaction is evolutionarily conserved from yeast to human, implying that it likely occurs under physiological conditions. Intriguingly, there is an increase in the translocation of VDAC1 under certain pathological conditions [ 46 , 52 ]. We propose that the association between EMC and VDAC1 may potentially strengthen under these abnormal conditions, and the EMC-VDAC1 complex may assist VDAC1 in translocation or carrying out non-classical functions.…”
Section: Discussionmentioning
confidence: 99%
“…VDAC1 biogenesis on the outer mitochondrial membrane is well-established and involves a complex pathway with the Tim/Tom import machinery, sTIM chaperones and the SAM/TOB complex [45]. Previous studies also unveiled that a portion of VDAC1 appears on other membrane systems [46][47][48][49], including the ER and plasm membrane [50][51][52], especially in conditions like type 2 diabetes [46], Alzheimer's disease [31], and virus infection [53]. However, the mechanism of VDAC1 translocation remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Staining using another anti-VDAC was strong in most layers (the ganglion cell layer was not in the picture) but weaker in the inner segments [ 29 ]. Another attempt to reveal the localization of VDAC1 showed strong staining in the inner segments, OPL, and IPL and faint staining in the somas in the INL [ 46 ]. The inconsistent staining patterns indicate that when using immunocytochemistry, most antibodies against VDAC are not sufficiently specific for the VDAC isoforms.…”
Section: Vdac Expression In Healthy Retinamentioning
confidence: 99%
“…While the precise localization of VDAC1 in the retina is still questionable, its function in retina was investigated by knocking it down using morpholino antisense RNA [ 46 ]. In these experiments, VDAC1 expression as measured by Western blots was reduced by about 45%, and this reduction greatly affected retinal structure: the retina was thinner, cells in the nuclear layers were undergoing apoptosis (as labeled by the TUNEL assay), and the number of three tested cell types (photoreceptors, horizontal cells, and ganglion cells, but not rod bipolar cells) was greatly reduced.…”
Section: Differential Functions Of Vdac Isoformsmentioning
confidence: 99%